Divergent Pd(II) and Au(III) mediated nitroalkynol cycloisomerizations - Patel, Pitambar; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2011)
A new cycloisomerization reaction comprising the simultaneous addition of nitro and alcohol groups across C C leading to skeletally diverse small molecules is documented.